The impact of corruption on governance: an appraisal of the practice of the rule of law in Kenya - Akonumbo, Atangcho Nji (University of Pretoria, 2006)
Prepared under the supervision of Dr. Atangcho N. Akonumbo at the Faculte de Sciences Sociales et de Gestion, Universite Catholique d'Afrique Centrale, Yaounde, Cameroon